Involving adolescents in evidence syntheses: an umbrella review - Azza Warraitch; Matylda Sulowska; Ciara Wacker; Maria Lee; Delali Bruce; Joshua Hernon; Qusai Khraisha; Kristin Hadfield (Systematic Reviews)
Abstract Background Stakeholder involvement in evidence syntheses has the potential to enhance the quality and relevance of reviews. However, adolescents rarely participate in evidence synthesis, mainly because their role and influence in shaping the synthesis process relating to health outcomes are poorly understood. To fully unlock the potential of evidence syntheses for adolescent health, it is crucial to understand how adolescents can contribute at various stages of the review process and how their involvement can influence outcomes. Methods To achieve this, we conducted an umbrella review examining adolescent involvement in reviews related to adolescent health research, complemented by a case study that highlights how adolescents were engaged at various stages of this review. We ran a search across 11 databases, screened reference lists and 12 journals, and consulted experts in youth involvement. Results We found only 10 reviews which involved adolescents. In those reviews, adolescents were engaged at almost every stage of the review process, with most involvement centred around interpreting findings or co-authoring the final reports. While adolescent participation was often consultative, there were examples of more collaborative involvement using a wide range of methods, even at technical stages like study selection and data analysis. However, reviews did not report on the impacts or benefits of adolescent involvement in evidence syntheses. Conclusion To maximise the impact of adolescent involvement, we call for engagement of adolescents throughout the review process and the adoption of frameworks to ensure transparency and consistency in reporting. Systematic review registration PROSPERO CRD42021287467.